ҚАРАҚАЛПАҚ ЕРТЕК ТИП СЮЖЕТЛИ ДӘСТАНЛАРЫНЫҢ ПАЙДА БОЛЫЎЫ ҲӘМ ҚӘЛИПЛЕСИЎИНДЕ ЕРТЕКЛЕРДИҢ ТУТҚАН ОРНЫ - Кеңесбаева, Ш.К. (ILIM hám JÁMIYET, 2023)
In the article, based on Karakalpak folk folklore, fairy tales are analyzed as a source of emergence and formation of epics, in particular epics with a fairy-tale plot. This point of view is discussed in detail on the example of the epic "Tulim Biy".